Multipurpose furniture wardrobe with iron table - Husin, Mohd Najib; Khairudin, Muhamad Salimi; Umar, Mohd Hanafi; Abdul Razak, Ahmad Amir (2010)
This project was conducted by final semester students of Diploma in Wood Industry. The objectives of the study are to solve the problem usually faced by bedroom based of limited space and saving the time during. Inspired by that, this new and compact wardrobe with iron table designed which come with five criteria which is modem, simple, adjustable, saving space and more functional. In other word, the product that we have build is a new idea of looking forward to the future that will create new market demand.